Edukasi Kesehatan Mengenai Pentingnya JANAT (Jajanan Sehat) terhadap Anak Sekolah Dasar - Steven Aldo Marcello; Ira Ayu Maryuti; Ermalynda Sukmawati; Made Indra Ayu Astarini (Jurnal Pengabdian Masyarakat (ABDIRA), 2026)
Healthy snacks are crucial for supporting the growth and development of elementary school-aged children. The high number of students consuming unhealthy snacks indicates the need for health education on the importance of healthy snacks. The education provided in this community service activity is JANAT (healthy snacks) using audiovisual media, with the aim of the information can be easily and effectively absorbed by primary student. After sequence of preparations from the initial survey and situation analysis, the activity was carried out for one day with 57 6th grade primary students participating. Evaluation of the activity results used pre- and post-test questionnaires, and the results showed that before receiving education, students' knowledge levels were at a good level (68.42%), moderate (31.58%). After receiving education, students' knowledge levels were at a good level (96.49%), moderate (3.51%). This indicates that there was an increase in knowledge among 6th grade primary students after receiving health education on the importance of JANAT.